Preparation method and application of Fe3O4@SiO2 photonic crystal organic gel

Through the combination of magnet control and thermal polymerization, a Fe3O4@SiO2 photonic crystal organic gel that can work normally under extremely harsh conditions was prepared, which solved the problem that photonic crystals cannot work in magnetic fields and harsh environments in the prior art, and achieved the bright structural color and excellent performance of the gel.

CN116693748BActive Publication Date: 2025-03-25YANGZHOU UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310442290.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-23
Publication Date
2025-03-25
Estimated Expiration
2043-04-23

AI Technical Summary

Technical Problem

Existing magnetically responsive colloidal photonic crystals cannot retain structural color without a magnetic field and cannot function properly in extremely harsh environments.

Method used

Through the method of magnet control and thermal polymerization, the one-step preparation of Fe3O4@SiO2 photonic crystal organic gel is achieved. The prepared gel has a bright structural color and maintains its performance under low temperature and vacuum environment.

Benefits of technology

It achieves that the gel can still work normally under extremely harsh conditions, with good flexibility, moisturizing properties and self-adhesion properties, and is suitable for display and sensing fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116693748B_ABST
    Figure CN116693748B_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a Fe3O4@SiO2 photonic crystal organic gel. The preparation method comprises providing a Fe3O4@SiO2 photonic crystal; uniformly dispersing the Fe3O4@SiO2 photonic crystal, a monomer, an initiator, and a cross-linking agent in an organic solvent to obtain a precursor solution; transferring the precursor solution to a container surrounded by magnetism, heating to initiate a polymerization reaction, and obtaining a Fe3O4@SiO2 photonic crystal organic gel. The polymerization reaction time of the invention is short, energy-saving, and pollution-free; through the combination of magnet control and thermal polymerization, the one-step preparation of the photonic crystal gel is achieved. The prepared gel has bright structural color, good flexibility in a low temperature environment, excellent moisture retention performance in a vacuum environment, excellent self-adhesion performance and self-healing performance, and has broad application prospects in the fields of display and sensing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional polymer material preparation, and specifically relates to a preparation method and application of Fe3O4@SiO2 photonic crystal organic gel. Background Art

[0002] Photonic crystals are a type of periodic dielectric material with a photonic bandgap structure. When the wavelength of light entering the photonic crystal material falls within the photonic bandgap, it will be completely reflected. At this time, the photonic crystal material will show a bright structural color. As long as this structure exists, the color will not disappear. Bright structural colors are widely present in nature and have important biological functions, including protection, reproduction, camouflage, avoidance and scaring off enemies. Magnetic responsive photonic crystals have attracted much attention due to their simple preparation, high saturation intensity, convenient magnetization, and rich responsiveness under external magnetic fields. They have broad application prospects in anti-counterfeiting, information encryption, magnetometers, and chemical sensors.

[0003] Magnetically responsive colloidal photonic crystals are usually composed of a core and a shell. Usually, the typical core is Fe3O4, and the shell is usually a high molecular polymer, such as polyacrylic acid, polyvinyl pyrrolidone, oleic acid, etc. The coating acts as an electrostatic stabilizer on the core surface, providing repulsive force during the accumulation of the external magnetic field. In addition, a layer of SiO2 shell is coated on the surface of the magnetic Fe3O4 to prevent the detachment of the polyelectrolyte. Under the action of an external magnetic field, the Fe3O4@SiO2 photonic crystal can display beautiful structural colors, but when the magnetic field is not applied, the structural color disappears, so how to successfully retain the structural color in the absence of a magnetic field becomes an important problem. In addition, currently magnetically responsive colloidal photonic crystals cannot work under extremely harsh conditions, so how to make photonic crystals work in extremely harsh environments remains a challenge. Summary of the invention

[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0006] One of the purposes of the present invention is to provide a method for preparing Fe3O4@SiO2 photonic crystal organic gel, which realizes the one-step preparation of photonic crystal gel by combining magnet control and thermal polymerization. The prepared gel has bright structural color and can still work normally under extremely harsh conditions.

[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing Fe3O4@SiO2 photonic crystal organic gel, comprising:

[0008] Provide Fe3O4@SiO2 photonic crystals;

[0009] The Fe3O4@SiO2 photonic crystal, monomer, initiator and cross-linking agent are uniformly dispersed in an organic solvent to prepare a precursor solution;

[0010] The precursor solution is transferred to a container with magnetic surroundings, and the polymerization reaction is initiated by heating to obtain Fe3O4@SiO2 photonic crystal organogel.

[0011] As a preferred scheme of the preparation method of Fe3O4@SiO2 photonic crystal organic gel of the present invention, the precursor solution includes, by mass fraction, 0.1-0.2% Fe3O4@SiO2 photonic crystals, 30-62.5% organic solvent, 0.2% cross-linking agent, 0.02-0.06% initiator, and the remainder is monomer.

[0012] As a preferred solution of the method for preparing the Fe3O4@SiO2 photonic crystal organogel of the present invention, the organic solvent is one of glycerol and ethylene glycol.

[0013] As a preferred solution of the method for preparing the Fe3O4@SiO2 photonic crystal organogel of the present invention, the monomer is a mixture of acrylamide and N-vinyl pyrrolidone in a mass ratio of 3:1.

[0014] As a preferred solution of the method for preparing the Fe3O4@SiO2 photonic crystal organogel of the present invention, the cross-linking agent is N,N'-methylenebisacrylamide.

[0015] As a preferred scheme of the preparation method of the Fe3O4@SiO2 photonic crystal organic gel of the present invention, the initiator is one of ammonium persulfate, tetramethylethylenediamine, 2-hydroxy-2-methyl-1-phenylpropanone, and 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone.

[0016] As a preferred solution of the method for preparing the Fe3O4@SiO2 photonic crystal organogel of the present invention, wherein: the heating to initiate the polymerization reaction has a heating temperature of 40 to 60°C.

[0017] As a preferred embodiment of the method for preparing Fe3O4@SiO2 photonic crystal organogel of the present invention, the method for providing Fe3O4@SiO2 photonic crystal comprises:

[0018] Providing Fe3O4 nanoparticles;

[0019] The Fe3O4 nanoparticles are used Methods SiO2 was coated to obtain Fe3O4@SiO2 photonic crystals.

[0020] As a preferred solution of the preparation method of the Fe3O4@SiO2 photonic crystal organic gel of the present invention, the particle size of the Fe3O4 nanoparticles is 80-180nm; the thickness of the coated SiO2 shell is 15-30nm; the particle size of the prepared Fe3O4@SiO2 colloidal nanoparticles is 120-210nm.

[0021] As a preferred embodiment of the method for preparing Fe3O4@SiO2 photonic crystal organogel of the present invention, the method for providing Fe3O4 nanoparticles specifically comprises:

[0022] Sodium citrate is dissolved in ethylene glycol, and then ferric chloride hexahydrate is dissolved in ethylene glycol. Ferric chloride hexahydrate is added to the original sodium citrate, and sodium acetate is added to fully dissolve it. The mixture is transferred into a reactor, heated to react, and after the reactor is cooled, magnetized and separated to obtain Fe3O4 nanoparticles.

[0023] As a preferred scheme for the preparation method of the Fe3O4@SiO2 photonic crystal organic gel of the present invention, the sodium citrate is dissolved in ethylene glycol in a 60°C water bath, the heating temperature in the reactor is 180-220°C, the heating time is 10 hours, and the particle size of the obtained Fe3O4 nanoparticles is 80-180nm.

[0024] As a preferred embodiment of the method for preparing Fe3O4@SiO2 photonic crystal organic gel of the present invention, the Fe3O4 nanoparticles are prepared by The method is to coat SiO2, and the specific method includes:

[0025] Fe3O4 nanoparticles were added to ethanol and water, stirred, and then ammonia water was added, and tetraethyl orthosilicate was added three times with an interval of 10 minutes and continued to stir to obtain Fe3O4@SiO2 colloidal nanoparticle particles with bright structural colors.

[0026] Another object of the present invention is to provide a Fe3O4@SiO2 photonic crystal organogel obtained by the preparation method described above.

[0027] Another object of the present invention is to provide the application of the Fe3O4@SiO2 photonic crystal organic gel as described above in the field of display and sensing, which does not freeze at -60°C, can retain moisture in a vacuum environment, and can still work normally under extremely harsh conditions.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The polymerization reaction time of the present invention is short, energy-saving and pollution-free; through the combination of magnet control and thermal polymerization, the one-step preparation of photonic crystal gel is realized, and the prepared gel has bright structural color, good flexibility in low temperature environment, excellent moisture retention performance in vacuum environment, excellent self-adhesion performance and self-healing performance. It has broad application prospects in the display and sensing fields, still does not freeze at -60°C, can retain moisture in a vacuum environment, and can still work normally under extremely harsh conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0031] Figure 1 This is a morphology observation diagram of the Fe3O4@SiO2 photonic crystal organogel obtained in Example 1 of the present invention;

[0032] Figure 2 This is the Fourier infrared spectrum of the Fe3O4@SiO2 photonic crystal organogel obtained in Example 1 of the present invention;

[0033] Figure 4 This is a graph showing the self-healing performance test results of gel columns of different colors assembled in Example 2 of the present invention;

[0034] Figure 5 This is a graph showing the self-healing performance test results of the cylindrical Fe3O4@SiO2 photonic crystal organogel after being cut in Example 2 of the present invention;

[0035] Figure 3 is a particle size diagram of the ferroferric oxide colloidal nanoparticles obtained in Example 3 of the present invention;

[0036] Figure 6 This is a DSC test result diagram of each Fe3O4@SiO2 photonic crystal organogel obtained with different glycerol contents in Example 4 of the present invention;

[0037] Figure 7 This is a graph showing the adhesion test results of various Fe3O4@SiO2 photonic crystal organogels obtained with different glycerol contents in Example 4 of the present invention;

[0038] Figure 8The actual pictures of the Fe3O4@SiO2 photonic crystal organogels obtained with different Fe3O4@SiO2 photonic crystal concentrations in Example 5 of the present invention;

[0039] Fig. 9 The actual pictures of the Fe3O4@SiO2 photonic crystal organogels obtained with different initiator concentrations in Example 7 of the present invention;

[0040] Fig.10 The actual pictures of the Fe3O4@SiO2 photonic crystal organogels obtained at different heating temperatures in Example 8 of the present invention;

[0041] Fig.11 This is a test result diagram of the moisture retention performance of the Fe3O4@SiO2 photonic crystal hydrogel obtained in Comparative Example 1 of the present invention;

[0042] Fig.12 This is a graph showing the adhesion test results of the Fe3O4@SiO2 photonic crystal organogel obtained in Comparative Example 2 of the present invention;

[0043] Fig.13 This is a graph showing the self-healing performance test results of the Fe3O4@SiO2 photonic crystal organogel obtained in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0044] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0045] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0046] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0047] Unless otherwise specified, the raw materials used in the examples were purchased commercially.

[0048] Example 1

[0049] (1) 0.618 g of sodium citrate was dissolved in 20 ml of ethylene glycol at 60°C. After cooling to room temperature, 0.819 g of ferric chloride hexahydrate dissolved in 10 ml of ethylene glycol was added thereto. After magnetic stirring for 30 min, 2.4 g of sodium acetate was added to the mixed solution. The mixture was stirred for 2 h to form a uniform colloidal solution. The obtained solution was transferred to a 50 ml reactor and reacted at 220°C for 10 h. After the reaction was completed, the reactor was cooled to room temperature and the obtained ferroferric oxide colloidal nanoparticles were washed three times with ethanol.

[0050] (2) Transfer the ferrosoferric oxide nanoparticles to a three-necked flask, add ethanol to 144 ml, then add 21.6 ml of distilled water, and mechanically stir at 50°C for 10 min at a speed of 180 r / min. Then add 14.4 ml of ammonia water and continue stirring for 15 min. Add tetraethyl orthosilicate three times, 120 μL each time, with an interval of 10 min, and continue stirring for 5 h to obtain Fe3O4@SiO2 colloidal nanoparticles with bright structural color. Wash the obtained product three times with ethanol, then wash it three times with distilled water and dry it.

[0051] (3) Take 0.01 g of colloidal photonic crystals and disperse them in 6 g of glycerol by ultrasonication for 30 min to form a uniform solution, to which 2.7 g of acrylamide, 0.9 g of N-vinyl pyrrolidone, 0.02 g of N,N'-methylenebisacrylamide and 0.003 g of ammonium persulfate are added and dispersed by ultrasonication for 30 min to form a uniform mixture. The obtained mixture is transferred to a rectangular mold, a magnet is placed at the bottom of the mold, and the polymerization is initiated by heating to 60 °C. The gel is peeled off from the mold to obtain a rectangular Fe3O4@SiO2 photonic crystal organogel.

[0052] The morphology of the structural color organogel was observed using SEM. Figure 1 As shown, Figure 1 (a) is a SEM image of the structural color organic gel at high magnification. It can be seen that Fe3O4@SiO2 is assembled into a one-dimensional chain structure inside the gel, which is why the gel can exhibit structural colors. Figure 1 (b) is the SEM image of the structural color organogel, where a typical three-dimensional network structure can be observed. Figure 1 (c) is a microscope picture of the structural color organic gel. Under the microscope, it can be clearly seen that there are a large number of one-dimensional chain structures inside the gel, which also explains why the gel can show bright structural colors.

[0053] Fourier transform infrared spectrometer was used to analyze the various components of the structural color organogel, such as Figure 2 As shown, the FT-IR spectrum of pure acrylamide is at 3349 cm -1The absorption peak at 3180cm is the asymmetric stretching vibration peak of -NH2. -1 The absorption peak at 1672cm is the symmetrical stretching vibration peak of -NH2. -1 The absorption peak at 1616cm is the stretching vibration peak of the C=O group. -1 The absorption peak at 3284 cm is the bending vibration of C=C or NH. -1 The absorption peak at 2935cm is the stretching vibration peak of -OH. -1 The absorption peak at 2880 cm-1 is the asymmetric stretching vibration peak of -CH2. -1 The absorption peak at 1109cm is the symmetrical stretching vibration peak of -CH2. -1 The absorption peaks at 1025 and 992 cm -1 The absorption peak at 1698 cm is the CO symmetric stretching vibration peak of the primary alcohol. In addition, the monomer 1-vinyl-2-pyrrolidone has an absorption peak at 1698 cm -1 The absorption peak at 1625cm is the stretching vibration absorption peak of the C=O group. -1 The absorption peak at 3200-3350cm is the stretching vibration peak of the C=C group. -1 The broad peak at 2935cm-1 indicates that the amino groups in acrylamide and the hydroxyl groups in glycerol can interact to form hydrogen bonds. This also shows that the good self-healing performance of the structural color organogel is due to the formation of hydrogen bonds. -1 、2880cm -1 、1025cm -1 and 992cm -1 The absorption peak at 1616cm -1 The absorption peak of C=C disappeared, indicating that C=C was destroyed in the process of preparing the structural color organogel.

[0054] Example 2

[0055] In this Example 2, based on Example 1, the content of sodium acetate in step (1) was adjusted to 1.8, 2.0, 2.2, 2.4 and 2.7 g, and the particle size of the ferroferric oxide colloidal nanoparticles obtained in step (1) was as follows: Figure 3 As shown, the evaluated particle sizes of the obtained ferrosoferric oxide colloidal nanoparticles were 150 nm, 160 nm, 180 nm, 245 nm, and 400 nm, respectively.

[0056] Subsequent experiments found that ferroferric oxide colloidal nanoparticles obtained with sodium acetate contents of 1.8, 2.0, 2.2 and 2.4 g can successfully prepare Fe3O4@SiO2 photonic crystal organogels, and all have structural colors.

[0057] However, the Fe3O4@SiO2 photonic crystal organogel prepared by the Fe3O4@SiO2 colloidal nanoparticles with a sodium acetate content of 2.7 g has a large particle size and does not have structural color.

[0058] Example 3

[0059] The precursor solution of photonic crystals with different particle sizes (150, 180, 245 nm) as obtained in Example 2 is transferred to a test tube, and after magnetic assembly, it is heated to induce polymerization to form gel columns of different colors, and red, green and yellow structural color organic gel columns are prepared. The gel columns of different colors are assembled together. The assembly steps are to cut the three prepared structural color hydrogel columns into small cylindrical blocks of almost the same shape and size with a knife, and arrange them together alternately and continuously according to different colors so that the contact surfaces are tightly combined. After a period of time, the spliced ​​mixed structural color gel cylinders are connected to each other, and finally successfully healed into a complete gel column, and its self-healing performance is tested. The test method is to stretch the assembled gel column axially, observe whether cracks are generated after stretching to a predetermined length, and then remove the tension to observe its recovery. The test results are as follows Figure 4 As shown. Among them, Figure 4 (a) is the original structural color organogel column, 4 cm long. Figure 4 (be) are pictures of gel columns stretched to 1 cm, 2 cm, 3 cm and 4 m respectively. Figure 4 (f) shows the gel column after recovery after stretching.

[0060] During the tensile deformation process, the cross section of the structural color organogel column did not crack ( Figure 4 (be)), indicating that the self-healing performance of the gel of the present invention is good. The stretched gel can recover to the length before deformation ( Figure 4 (f)), indicating that the gel has good mechanical properties.

[0061] The middle of the Fe3O4@SiO2 photonic crystal organic gel column obtained by the present invention was cut with a knife, and squeezed from both sides to the middle crack. After squeezing for a period of time, it was stretched to both sides to observe the healing condition of the cross section. The test results are as follows: Figure 5 It can be seen that the Fe3O4@SiO2 photonic crystal organic gel obtained by the present invention only takes 1 second to be squeezed from the cross section, and no cracks will appear at the cross section after stretching, and has extremely strong self-healing performance.

[0062] Example 4

[0063] In this embodiment 4, on the basis of embodiment 1, glycerol was used to adjust the mixed solvent of glycerol and water, and the volume ratio of glycerol to water was set to 0:10, 3:7, 5:5, 7:3 and 10:0. The obtained Fe3O4@SiO2 photonic crystal organogels were subjected to DSC test. The test results are as follows: Figure 6 shown.

[0064] Depend on Figure 6 It can be seen that when the glycerol content of the solvent is less than 30%, the gel has a freezing point at -29°C and its antifreeze ability decreases. No freezing point appears in DSC, which can prove that the gel still does not freeze at -60°C.

[0065] The adhesion of each Fe3O4@SiO2 photonic crystal organogel was tested. The test results are as follows: Figure 7 shown.

[0066] Depend on Figure 7 It can be seen that with the increase of glycerol content in the mixed solvent, the adhesion force of Fe3O4@SiO2 photonic crystal organogel gradually increases, and when the solvent is pure glycerol, the adhesion force can reach 40.4 kPa.

[0067] Example 5

[0068] In this embodiment 5, based on the embodiment 1, the proportion of Fe3O4@SiO2 photonic crystal was adjusted to 0.05%, 0.1%, 0.15%, 0.2% and 0.25% respectively, and pictures of the obtained Fe3O4@SiO2 photonic crystal organogels were collected. The test results are as follows: Figure 8 shown.

[0069] Depend on Figure 8 It can be seen that when the Fe3O4@SiO2 mass ratio is lower than 0.1%, the gel cannot produce structural color; when the mass ratio is higher than 0.2%, the structural color deteriorates.

[0070] Example 6

[0071] In Example 6, the content of the crosslinking agent is adjusted on the basis of Example 1. Experiments show that when the content of the crosslinking agent is less than 0.1%, no gel can be formed; when the content is higher than 0.2%, the gel becomes very hard.

[0072] Example 7

[0073] In Example 7, based on Example 1, the proportion of initiator was adjusted to 0.02%, 0.04%, 0.06%, and 0.08%, respectively, and pictures of the obtained Fe3O4@SiO2 photonic crystal organogels were collected. The test results are as follows: Fig. 9 shown.

[0074] Depend on Fig. 9It can be seen that when the initiator content is less than 0.02%, the initiation rate is too slow; when it is higher than 0.06%, the gel is prone to violent polymerization.

[0075] Example 8

[0076] In Example 8, based on Example 1, the heating temperatures in step (3) were adjusted to 20°C, 40°C, 60°C, and 80°C, respectively, and pictures of the obtained Fe3O4@SiO2 photonic crystal organogels were collected. The test results are as follows: Fig.10 shown.

[0077] Depend on Fig.10 It can be seen that when the temperature is lower than 40°C, the initiation rate is too slow and polymerization may not even occur; when the temperature is higher than 60°C, the initiation rate is too fast and polymerization is likely to occur violently.

[0078] Comparative Example 1

[0079] In this comparative example 1, on the basis of Example 1, the glycerol in step (3) was replaced by water, 0.01 g of colloidal photonic crystals were dispersed in 6 g of water by ultrasonication for 30 min to form a uniform solution, to which 2.7 g of acrylamide, 0.9 g of N-vinyl pyrrolidone, 0.02 g of N,N'-methylenebisacrylamide and 0.003 g of ammonium persulfate were added to obtain Fe3O4@SiO2 photonic crystal hydrogel.

[0080] The moisturizing properties of the Fe3O4@SiO2 photonic crystal hydrogel were tested. The test results are as follows: Fig.11 As shown, Figure (a) is a picture of a structural color gel with a glycerol content of 60% placed at room temperature for five days; Figure (b) is a picture of the hydrogel of Comparative Example 1 placed at room temperature for five days.

[0081] From the figure, we can see that when the proportion of glycerol is 60%, the gel has good moisturizing properties, and the structural color can be well preserved, extending the service life of the photonic crystal; when the gel does not contain glycerol, the gel begins to shrink and deform after being placed at room temperature for five days.

[0082] Comparative Example 2

[0083] In this comparative example 1, glycerol in step (3) is replaced by ethylene glycol, and the other steps are the same as those in Example 1. The obtained Fe3O4@SiO2 photonic crystal organogel is subjected to an adhesion test. The test method is to stick one side of the disc-shaped organogel to glass and the other side to a heavy magnet, and then lift the other end of the glass. The adhesion test results of this comparative example 2 and Example 1 are shown as follows: Fig.12 As shown. It can be seen that the glycerol-based photonic crystal gel can stick to heavy objects ( Fig.12 a), while ethylene glycol-based photonic crystal gel cannot stick to heavy objects and slides off ( Fig.12 b) The adhesion performance of the Fe3O4@SiO2 photonic crystal organogel obtained in Comparative Example 2 is inferior to that of the Fe3O4@SiO2 photonic crystal organogel in Example 2.

[0084] The obtained Fe3O4@SiO2 photonic crystal organogel was tested for self-healing according to the method in Example 2. The test results are as follows: Fig.13 It can be seen that after the cross section is healed, the organogel is stretched again and the healed cross section is broken again, indicating that the self-healing property of the Fe3O4@SiO2 photonic crystal organogel obtained in this comparative example 2 is not as good as that of the Fe3O4@SiO2 photonic crystal organogel in Example 2.

[0085] The present invention adopts a hydrothermal method to prepare 120-210nm Fe3O4@SiO2 colloidal nanoparticles, and quickly prepares Fe3O4@SiO2 photonic crystal organogel by thermal initiation polymerization. The method is simple and has low energy consumption. The preparation of Fe3O4@SiO2 photonic crystal gel can be completed within 5-10 minutes. By simply controlling the direction of the magnet, the diffraction direction of the photonic crystal organogel can be changed, and finally a cylindrical and patterned Fe3O4@SiO2 photonic crystal organogel is obtained. This method combines magnetic field assembly with thermal polymerization, and completes the preparation of Fe3O4@SiO2 photonic crystal organogel in one step in a short time, solving the problems of the traditional Fe3O4@SiO2 photonic crystal gel preparation process being cumbersome, time-consuming and energy-consuming. At the same time, the gel has broad application prospects in the fields of antifreeze and moisturizing, and still does not freeze at -60°C, can moisturize in a vacuum environment, and can still work normally under extremely harsh conditions.

[0086] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A method for preparing Fe3O4@SiO2 photonic crystal organogel, characterized in that: include, Provide Fe3O4@SiO2 photonic crystals; The Fe3O4@SiO2 photonic crystal, monomer, initiator and cross-linking agent are uniformly dispersed in an organic solvent to prepare a precursor solution; The precursor solution is transferred to a container with magnetic surroundings, and the polymerization reaction is initiated by heating to obtain Fe3O4@SiO2 photonic crystal organogel; The precursor solution includes, by mass fraction, 0.1-0.2% of Fe3O4@SiO2 photonic crystals, 30-62.5% of organic solvent, 0.2% of crosslinking agent, 0.02-0.06% of initiator, and the remainder is monomer; The organic solvent is glycerol; The monomer is a mixture of acrylamide and N-vinyl pyrrolidone in a mass ratio of 3:1; The initiator is ammonium persulfate; The heating initiates the polymerization reaction, and the heating temperature is 40-60°C; during the preparation of the Fe3O4@SiO2 photonic crystal organic gel, the particle size of the Fe3O4 nanoparticles is 80-180nm; the thickness of the coated SiO2 shell is 15-30nm; the particle size of the Fe3O4@SiO2 photonic crystal colloidal particles is 120-210nm.

2. The method for preparing the Fe3O4@SiO2 photonic crystal organogel according to claim 1, characterized in that: The cross-linking agent is N,N'-methylenebisacrylamide.

3. The method for preparing the Fe3O4@SiO2 photonic crystal organogel according to any one of claims 1, characterized in that: The specific method of providing Fe3O4@SiO2 photonic crystals includes: Providing Fe3O4 nanoparticles; The Fe3O4 nanoparticles are used Methods SiO2 was coated to obtain Fe3O4@SiO2 photonic crystals.

4. Application of the Fe3O4@SiO2 photonic crystal organogel obtained by the preparation method according to any one of claims 1 to 3 in the field of display and sensing, characterized in that: The Fe3O4@SiO2 photonic crystal organic gel does not freeze at -60°C and maintains vacuum moisture retention.

Citation Information

Patent Citations

  • Magnetically-assembled photonic crystal hydrogel film, and preparation method and application thereof in air humidity sensor

    CN114085399A